Quality assessment of mangrove growing environment in Pasuruan of East Java - Edyson Indawan; Ricky Indri Hapsari; Kgs Ahmadi; Dian Noorvy Khaerudin (Journal of Degraded and Mining Lands Management, 2017)
The occurrence of pollution in mangrove land is due to changes in physical, chemical and biological properties of water because of the increasing human activities that produce problems due to residential and industrial wastes and other related activities, or due to seawater tide. The existence and presence of residential and industrial wastes in soil sediments can disturb the environment that in turn will threaten mangroves growth. This study was aimed to reveal the presence of heavy metals in sediment shown by environmental changes of water polluted by residential and industrial wastes. The study was conducted in field plots located at five watershed areas of Andil, Porangan, Kacar, Gombal and Krondo in Tambak Lekok Village of Pasuruan District, East Java. Field exploration and observation was started from waterfront and riverside vegetations. The exploration was made 300 m toward inland, perpendicular to the edge of the waters. The sediment samples of mangrove stands were collected at three points for each plot. The thickness of the collected sediment samples was ± 10 cm from the surface. Sediment samples were analyzed for heavy metals (Pb, Cr, Zn and Cu) and texture. The results showed that the Pb severely polluted the Gombal watershed with a concentration of 7.24mg/kg. The lowest Pb concentration of 7.24 mg/kg was observed for Andil watershed. Except for Andil watershed, Cu heavily polluted all the watersheds studied